TEACHER'S TREATMENT OF GENDER ISSUES PRESENTED IN TEXTBOOK TEXTS - Hindasah, Helmi (2016)
Most research under the topic of gender and foreign language textbooks have been focused solely on texts. One thing that seems to have been missed is an exploration of teacher behavior in relation to textbook texts, which actually cannot be predicted. Thus, the research is aimed at investigating the ways in which the teacher treats gender issues presented in the textbook texts as learning materials. It also explored the topic of gender, in relation to classroom interaction. The research utilizes qualitative descriptive case study focusing on a set of lessons in which the textbook used presented some aspects of gender. Data was collected from several classroom observations in all-male students and mixed students classes, as well as semi-structured interview with the teacher. The data shows that the texts used in the classroom are considered as texts which maintain traditional representation of gender roles where the teacher mostly endorses the idea. The data also revealed that the teacher ignores the discussion of possible gender issues and his treatment was somewhat unclear. From a feminist post-structuralist discourse analysis perspective, competing discourses of gender differentiation and collaborative talk, actually work through the institution of the classroom. So this means that the teacher has not yet consider "gender issue" in textbooks essential to be discussed with the students in the classroom. Thus, it is recommended that teachers should develop their awareness towards gender issues to have greater implication inside and outside of the classroom. Keywords: Teacher's Treatment, Gender Issues, Textbook Texts, FPDA (Feminist Post-Structuralist Discourse Analysis)   Teacher's Treatment of Gender Issues Presented in Textbook Texts Sebagian besar penelitian dengan topik gender dan buku paket bahasa asing hanya berfokus pada teks. Satu hal yang terlupakan yaitu eksplorasi perlakuan guru terhadap teks, yang tidak dapat diprediksi. Karenanya, penelitian ini bertujuan untuk menginvestigasi cara guru memperlakukan isu-isu gender yang terdapat dalam buku paket sebagai bahan ajar. Penelitian ini juga mengeksplor topik gender yang berkaitan dengan interaksi di dalam kelas. Penelitian ini menggunakan qualitative descriptive case study yang berfokus pada satu set pembelajaran dimana teks yang digunakan menampilkan isu-isu gender di dalamnya. Data diperoleh dari beberapa observasi di kelas laki-laki dan kelas campur, serta wawancara semi-struktur dengan guru. Data menunjukkan bahwa teks yang digunakan dianggap sebagai teks yang mempertahankan (maintain) representasi tradisional dari peran gender dimana guru sebagian besar mendukung (endorses) ide tersebut. Data juga menunjukkan bahwa guru tersebut mengabaikan (ignores) diskusi kemungkinan isu-isu gender dan perlakuannya tidak jelas (unclear). Dari sudut pandang Feminist Post-Structuralist Discourse Analysis, persaingan discourse dalam hal perbedaan gender dan percakapan kolaboratif, benar terjadi di dalam kelas. Hal ini bearrti bahwa guru tersebut belum menganggap isu gender dalam buku paket pentingn untuk didiskusikan bersama siswa. Karenanya, disarankan bahwa guru-guru harus mengembangkan kesadaran mereka terhadap isu-isu gender untuk memperoleh implikasi yang lebih besar di dalam dan di luar kelas. Kata kunci: Perlakuan Guru, Isu-isu gender, Buku Paket, FPDA (Feminist Post-Structuralist Discourse Aanalysis)